Multilayered polyelectrolyte-coated gold nanorods as multifunctional optical contrast agents for cancer cell imaging - Chen, Li-li (Zhejiang University Press, 2010)

(untitled)
We report the application of multilayered polyelectrolyte-coated gold nanorods (GNRs) as multifunctional optical contrast agents for cancer cell imaging. The surface modification of GNRs improves their chemical stability and facilitates them to be taken up by cancer cells through electrostatic interaction. The unique longitudinal surface plasmon resonance property of GNRs makes them suitable as both “scattering contrast agents” and “Raman contrast agents”. In our experiments, the staining of GNRs in cells was further confirmed by dark field microscopy and Raman microscopy. Our experiment results indicated that GNRs have great potential as multifunctional “optical contrast agents” for future in vivo animal imaging.